Characteristics of type 2 diabetes mellitus patients at Puskesmas Sanden: A cross sectional study - Sari Dina Fitria; Sukirto Novi Wijayanti; Arifin Zainul; Devi Noor Rahmawati Evita; Irmawan Rano; Yuniasih Dewi; Masduki Imam (BIO Web of Conferences)
Type 2 diabetes mellitus (T2DM) is a chronic disease characterized by insulin resistance and hyperglycemia. T2DM is a serious public health problem with increasing prevalence throughout the world. In Indonesia, the prevalence of type 2 diabetes mellitus is estimated at 10,3%. This study aims to determine the characteristics of type 2 diabetes mellitus patients at Puskesmas Sanden. This research is a descriptive observational study with a cross sectional approach. Data was collected from medical records of patients with T2DM at Puskesmas Sanden. Data were collected from medical records of T2DM patients in Puskesmas Sanden. A total of 96 respondents fulfilled the inclusion and exclusion criteria. The majority of T2DM patients were female (56.3%) and aged 51-65 years (51.0%). Hypertension was the most common comorbidity (63.0%). Many patients experienced complications such as nephropathy diabetic (4.0%), ophtalmic disease (9.0%), neuropathy diabetic (13.0%) and vascular disease (17.0%). T2DM is a serious disease with a high prevalence and can cause dangerous complications.